Prognosis Factors in Patients with Non-Hodgkin’s Lymphoma Presenting with Gastrointestinal Tract Symptoms - Brian H Weinerman; Brendan MacDougall; Ian Carr (Canadian Journal of Gastroenterology)
Forty-one individuals who presented with symptoms referable to the gastrointestinal tract were extracted from the authors’ total review of non-Hodgkin’s lymphoma in Manitoba from 1968 through 1978. Only cases at stages I to III were included, and there were 22 males and 19 females. Sixteen non-Hodgkin’s lymphomas arose in the small bowel, 15 in the stomach and 10 in the colon. The natural history of this group of gastrointestinal non-Hodgkin’s disease is described, and univariate and multivariate analyses were done using the variables of sex, pathology, stage, resection, site of disease and initial chemotherapy. The median survival of the group was 28 months. Sex and stage appeared to be important prognostically, but after multivariate analysis, only the female sex appear to be a good prognostic variable. There was a suggestion that resection should be attempted in these lesions, but there was not a large sample size in this group. In addition, it was felt that this group of individuals followed the same survival pattern as did poor prognosis non-Hodgkin’s lymphomas of nongastrointestinal origin.